Pseudorandom Sequences Classification Algorithm - Spirin, Andrey; Kozachok, Alexander (Journal of Science and Technology on Information security, 2021)
Abstract—Currently, the number of information leaks caused by internal violators has increased. One of the possible channels for information leaks is the transmission of data in encrypted or compressed form, since modern DLP (data leakage prevention) systems are not able to detect signatures and other information related to confidential information in such data. The article presents an algorithm for classifying sequences formed by encryption and compression algorithms. An array of frequencies of occurrence of binary subsequences of length N bits was used as a feature space. File headers or any other contextual information were not used to construct the feature space. The presented algorithm has shown the accuracy of classification of the sequences specified in the work 0.98 and can be implemented in DLP systems to prevent the transmission of information in encrypted or compressed form. Tóm tắt—Hiện nay, số vụ rò rỉ thông tin bởi đối tượng vi phạm trong nội bộ gây ra ngày càng gia tăng. Một trong những kênh có thể dẫn đến rò rỉ thông tin là việc truyền dữ liệu ở dạng mã hóa hoặc nén, vì các hệ thống chống rò rỉ dữ liệu (DLP) hiện đại không thể phát hiện chữ ký và thông tin trong loại dữ liệu này. Nội dung bài báo trình bày thuật toán phân loại các chuỗi được hình thành bằng thuật toán mã hóa và nén. Một mảng tần số xuất hiện của các chuỗi con nhị phân có độ dài N bit được sử dụng làm không gian đặc trưng. Tiêu đề tệp hoặc bất kỳ thông tin ngữ cảnh nào khác không được sử dụng để xây dựng không gian đối tượng. Thuật toán được trình bày có độ chính xác trong việc phân loại các chuỗi đạt 0,98 và có thể được áp dụng trong các hệ thống DLP để ngăn chặn việc rò rỉ thông tin khi truyền thông tin ở dạng mã hóa hoặc nén.